2010
DOI: 10.1186/1471-2334-10-241
|View full text |Cite
|
Sign up to set email alerts
|

The Microfloral Analysis of Secondary Caries Biofilm around Class I and Class II Composite and Amalgam Fillings

Abstract: BackgroundSecondary caries is responsible for 60 percent of all replacement restorations in the typical dental practice. The diversity of the bacterial sources and the different types of filling materials could play a role in secondary caries. The aim of this study was to determine and compare the microbial spectrum of secondary caries biofilms around amalgam and composite resin restorations.MethodsClinical samples were collected from freshly extracted teeth diagnosed with clinical secondary caries. Samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 27 publications
(26 reference statements)
1
36
0
4
Order By: Relevance
“…These results might suggest that composites lead to certain changes in the dental biofilm favoring the outgrowth of more cariogenic species. On the other hand, a study by Mo et al [68] showed that neither the type of restorative material nor the location of the SC lesion have a significant effect on the microbiota under the restoration. However, it should be emphasized that in all reviewed studies, the composition of dental biofilms was determined using traditional microbiological techniques consisting of cultivation of microorganisms on different selective and non-selective agar plates and subsequent identification by physiological, biochemical and serological tests.…”
Section: Fig 4 -Histopathology Of Secondary Caries Lesions Next To Cmentioning
confidence: 97%
“…These results might suggest that composites lead to certain changes in the dental biofilm favoring the outgrowth of more cariogenic species. On the other hand, a study by Mo et al [68] showed that neither the type of restorative material nor the location of the SC lesion have a significant effect on the microbiota under the restoration. However, it should be emphasized that in all reviewed studies, the composition of dental biofilms was determined using traditional microbiological techniques consisting of cultivation of microorganisms on different selective and non-selective agar plates and subsequent identification by physiological, biochemical and serological tests.…”
Section: Fig 4 -Histopathology Of Secondary Caries Lesions Next To Cmentioning
confidence: 97%
“…1,2 However, many tooth-coloured restorations have been replaced because of secondary caries, which is responsible for 60% of all restoration replacements in typical dental practice. 3,4 One of the important causative factors in the development of secondary caries is the accumulation of dental biofilms adjacent to the margins of restorations, which causes dissolution of the adjacent tooth surfaces and finally shortens the serving life of the restorations. 5,6 If dental biofilms are allowed to remain on tooth surfaces or margins of restorations with the frequent consumption of a high carbohydrate diet, Streptococcus mutans, as a constituent of the biofilm community, will continue to synthesize extracellular polysaccharides (EPS) and metabolize the sugars to organic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the antimicrobial activities of polymerized resin disks prepared from comonomer blends with bis-GMA:TEGDMA:QAMS-3 PH mass ratios of 70:30:0, 70:10:20 and 70:0:30 were investigated using single-species biofilms of Streptococcus mutans (ATCC 36558), Actinomyces naeslundii (ATCC 12104) or Candida albicans (ATCC 90028). The first two represent cariogenic oral pathogens that are associated with recurrent decay around tooth fillings [44]. Candida albicans , a common commensal fungus in humans, may be converted to an opportunistic pathogen associated with oral candidiasis in susceptible hosts [45].…”
Section: Discussionmentioning
confidence: 99%